PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT BERBASIS QUIZIZZ PAPER MODE TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA KELAS IV SD - Mutiara Putri; Dayu Rika Perdana; Roy Kembar Habibi; Annisa Yulistia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The problem of this research is the low learning outcomes of Pancasila Education in grade IV at SD Negeri 1 Natar. This research aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model based on Quizizz Paper Mode on Pancasila Education learning outcomes. The research method used is a quasi-experiment with a nonequivalent control group design. The population consists of 112 students, and the sample used includes 29 students from grade IV A and 27 students from grade IV B, the sample are determined using purposive sampling. The data collection techniques uses tests in the form of pretests and posttests as well as non-tests in the form of observations. The data were analyzed using a simple linear regression test, and the result of 0.00<0.05 indicates that H0 is rejected and Ha is accepted. The result of this research represent that there is an effect of implementing the Teams Games Tournament cooperative learning model based on Quizizz Paper Mode on the learning outcomes of Pancasila Education for Grade IV students at SD Negeri 1 Natar in the 2025/2026 academic year.